Influence After the Birth of Romanticism in the World of Arabic Literature - Febrianisa, Sindy (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
After the emergence of the Romanticism School which experienced rapid development in the world of Arabic literature. It has had a major impact on changes in literary genres, especially after the emergence of the Romantic School had an influence so that literary works experienced a very significant shift. This provides an illustration of how the arrival of Romanticism in the world of Arabic literature can change the genre of literature which was originally only born of thoughts and then changed to be more inclined towards feeling and emotion. The research uses the literature study method with a qualitative descriptive approach. The technique used is the technique of observing and noting. The results that have been obtained are that with the development of romanticism in Arabic literature, which was first brought by Napoleon in the 20th century, it was considered as a criticism of the previous school, and has had a very strong influence on literature. Which with the birth of this school then developed until the emergence of groups that criticized the classical school made changes to the genre of literature which was initially very rationalism and realism, then changed to be very different so that emphasizing taste and emotion became the main points in this school.